(untitled) (Modern American Journal of Medical and Health Sciences, 2025)
In the context of the ecological crisis in the Aral Sea region (dust storms, water mineralization, and intense insolation), a study was conducted to investigate the risk factors for the development and progression of chronic kidney disease (CKD). At the first stage, 500 residents of the region (aged 25–65) underwent a screening questionnaire using a modified scoring system that included both traditional risk factors (arterial hypertension, diabetes mellitus, obesity, smoking) and region-specific "non-traditional" factors (proximity to the Aral Sea, drinking water source, level of insolation). In 115 patients with high or moderate risk (based on the questionnaire), CKD stages II–IV were verified, and a 6-month follow-up was initiated with monitoring of GFR and ultrasound. In parallel, data from 217 CKD patients from primary healthcare settings were analyzed. The results showed.